2020
DOI: 10.1016/j.heliyon.2020.e03863
|View full text |Cite
|
Sign up to set email alerts
|

Identification of markers for the authentication of cranberry extract and cranberry-based food supplements

Abstract: Due to the high cost of the cranberry extract, there have been several reported cases of adulteration. The aim of our study was to find markers to authenticate extracts or cranberry-based food supplements. Cranberry fruits from 7 countries, 17 cranberry extracts and 10 cranberry-based food supplements were analysed by UPLC-DAD-Orbitrap MS. Procyanidins were assessed by DMAC method. Anthocyanin fingerprint and epicatechin/catechin, procyanidin A2/total procyanidin and procyanidin/anthocyanin ratios were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…Cranberries also have anti-adhesion properties for urinary pathogens and antioxidant properties (Hisano et al 2012 ). The active biological compounds present in the cranberries include xyloglucan oligosaccharides such as arabinoxyloglucan oligosaccharides and pectic oligosaccharides (Gardana et al 2020 ). Cranberries maintain gut health and oral health.…”
Section: Functional Foodmentioning
confidence: 99%
“…Cranberries also have anti-adhesion properties for urinary pathogens and antioxidant properties (Hisano et al 2012 ). The active biological compounds present in the cranberries include xyloglucan oligosaccharides such as arabinoxyloglucan oligosaccharides and pectic oligosaccharides (Gardana et al 2020 ). Cranberries maintain gut health and oral health.…”
Section: Functional Foodmentioning
confidence: 99%
“…Gardana et al have studied the anthocyanin content in fruit samples of ‘Ben Lear’, ‘Howes’, ‘Stevens’, and ‘Bergman’ cultivars and found that the total anthocyanin content ranged from 2.4 mg/g to 5.6 mg/g [ 44 ]. The total anthocyanin levels (5.07 mg/g in cranberry samples of the ‘Howes’ cultivar and 3.36 mg/g in cranberry samples of the ‘Bergman’ cultivar) that were found by the authors were lower than those found in our study (6.80 mg/g and 5.34 mg/g in fruit samples of the ‘Howes’ and ‘Bergman’ cultivars, respectively) [ 44 ]. Brown et al have examined the anthocyanin composition in fruit samples of cultivars ‘Ben Lear’, ‘Bergman’, ‘GH 1’, ‘Pilgrims’, and ‘Stevens’ and found that the total anthocyanin content ranged from 2.81 mg/g to 7.98 mg/g [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PLS showed good performance in detecting the level of adulteration in cranberry extracts. However, because polyphenolic profiles may not be sufficient alone to detect adulteration, especially if it happens by the addition of raw materials devoid of polyphenolic compounds, Gardana et al (2020) focused on finding other markers for detecting adulteration in cranberry extracts. By using ACN fingerprints, as well as epicatechin/catechin, procyanidin A2/total anthocyanidin, and procyanidin/ACN ratios, adulteration was detected in four commercial extracts and six food supplements.…”
Section: Lc-based Authentication Of Vaccinium Speciesmentioning
confidence: 99%